Utilization of Fly Ash as Incorporate Material to Produce Construction Bricks Through Firing Method - Zakaria, Muhammad Ibrahim; Jamellodin, Zalipah (Recent Trends in Civil Engineering and Built Environment, 2022)
Brick is one of the most important structural elements in construction work that helps to support the structure of the building. Today, practically every country uses bricks to construct buildings, and around 30% of the world’s population still lives in earthen structures that were once used as shelters. The management of waste products is one of the world’s most serious environmental challenges. Thermal power facilities generate a lot of waste, primarily in the form of ash, which can be harmful if not properly managed. The purpose of this study is to review the production bricks by utilizing the waste material, which is fly ash (FA) by through a conventional firing method. Based on the previous research, this review study would concentrate on the effect of the addition of FA in clay brick toward its compressive strength and water absorption by using various firing temperature rates. Besides, this study also would discuss the suitable percentage of FA contenting in clay brick and the optimal firing temperature used by the previous researcher in their research to obtain the best result in terms of mechanical and durability of the incorporating FA brick. Despite many studies, commercial manufacture of bricks from waste materials remains extremely limited. The slow acceptance of waste-based bricks by industry and the public could be one of the reasons. Therefore, insistence on the both domestic and foreign construction industry to plays a decisive role to promote and utilise waste material such as FA in FA-clay incorporated brick production.